Writing Thesis in English Education: Challenges Faced by Students - Tiwari, Hari Prasad (Journal of NELTA Gandaki, 2019)
A thesis is the most important write up in a researcher's life. Writing the research document in the form of a thesis is considered as the most challenging among the students. Keeping this view in mind, the present study was conducted to investigate the major challenges facing by the students of Masters of Education (M. Ed.) in English under Tribhuvan University (T.U.) while writing thesis. Fifteen students who have submitted the final draft of thesis in the Department of English Education of their respective campuses in partial fulfillment of M.Ed. in English and waiting for viva-voce were selected employing non-random purposive sampling procedure. The researcher used interview as a tool to collect the data which included open ended questions only. Interviews were audio recorded and they were transcribed, thematized and presented in narrative form. The findings were presented employing descriptive technique of qualitative data analysis. The findings of the study revealed that unsupportive behavior of the supervisors and difficulties of selecting the appropriate field or area of the study are major challenges while writing the thesis in English Education.